The Husband’s Absolute Authority in Nikah Sirri: An Analysis of Maqāṣid al-Syarī’ah on Women’s Rights - Hanafi, Sahrul; Akhmadi, Nurman; Ahmad Saebani, Beni; Fautanu, Idzam (Civiliza Publishing, 2026)
The practice of nikah sirri in Indonesia often results in the husband’s absolute authority, which is detrimental to women due to the lack of state legal protection. This study aims to analyze the impact of such authority on women’s rights through the perspective of Maqāṣid al-Syarī’ah and to propose a reconstruction of family law. The method employed is normative legal research with an ecosentric approach, examining laws, legal concepts, and court rulings. The results of the study indicate that absolute authority in secret marriages disrupts the family justice ecosystem and violates the principles of Maqāṣid, particularly the protection of life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Women face structural vulnerabilities in the form of the loss of maintenance rights, shared property, and the legal status of their children. In conclusion, this practice contradicts the spirit of substantive Islamic justice. A legal reconstruction is needed to strengthen the role of the state and judges as guardians of the balance of the justice ecosystem, as well as a reinterpretation of the concept of qiwamah based on consultation and gender justice. Marriage registration must be viewed as a Sharia instrument to guarantee human dignity, not merely an administrative formality.